Enhancing Smoking Cessation Support: Audit of Nicotine Replacement Therapy (NRT) in Psychiatric Inpatient Care - Nikhil Gauri Shankar; Hadiya Kar; Wamiqur Rehman; Aanika Hoque; Ishraq Elahi; Charles Okwuchi; Rajkumar Reddy (BJPsych Open)
Aims: This audit aimed to evaluate the prescription practices of Nicotine Replacement Therapy (NRT) in adult psychiatry inpatient wards in North Wales. Given the high prevalence of smoking among individuals with mental health disorders, the Welsh Government’s legislation mandating smoke-free hospital grounds underscores the importance of effective NRT use to support smoking cessation and improve mental and physical health outcomes. Specifically, the audit assessed adherence to key standards, including timely provision of NRT, assessment of smoking status, and documentation of contraindications and drug interactions.